The clinical value of combination of immune checkpoint inhibitors in cancer patients: A meta‐analysis of efficacy and safety. Issue 12 (30th August 2017) - Wu, Yingcheng; Shi, Hui; Jiang, Maorong; Qiu, Mingyan; Jia, Keren; Cao, Tianyue; Shang, Yujuan; Shi, Lili; Jiang, Kui; Wu, Huiqun
Abstract : The use of immune checkpoint inhibitors (ICIs) in combination therapy is an emerging trend in tumor immunology. However, the value of combination immunotherapy remains controversial, because of the toxic effects induced by combination. The added benefit of each additional drug has not been assessed against the added toxicity. We searched for clinical trials that evaluated ICI monotherapies and combination therapies in lung cancer and melanoma patients. The overall response rate (ORR), grade 3/4 treatment‐related adverse event rate, overall survival (OS), and progression‐free survival (PFS) were extracted from the most recently published studies to determine the relative risk (RR), hazard ratios (HRs), and 95% confidence intervals (CIs). Seven randomized controlled trials and one open‐label study were identified ( n = 3, 097). Treatments included combinations of several ICIs, a combination of an ICI and dacarbazine, two combinations of an ICI, paclitaxel and carboplatin, and a combination of an ICI and gp100 vaccine. Higher ORR (RR: 1.51, 95% CI: 1.03–2.20, p = 0.034), OS (HR: 0.86, 95% CI: 0.78–0.95, p = 0.000), and PFS (HR: 0.93, 95% CI: 0.72–1.14, p = 0.000) values were observed in combination therapy than in monotherapy. In addition, the toxicity of combination ICI immunotherapy was higher (RR: 1.50, 95% CI: 1.03–2.19, p = 0.036) than that of monotherapy. This meta‐analysis showed that the addition of nivolumab to ipilimumab better benefits PFS and ORR. Adding sargramostim was associated with better OS and safety. The efficacy and safety of a nivolumab‐ipilimumab‐sargramostim combination should be investigated further. Abstract : What's new? Immune checkpoint inhibitors (ICIs) are robust antitumor agents that have been explored extensively in clinical trials as monotherapy for different cancer types. Recent studies have begun to also examine ICI use in combination immunotherapy, though whether the benefits outweigh potential toxicities remains uncertain. This meta‐analysis suggests that in lung cancer and melanoma patients, overall survival, progression‐free survival, and overall response rate can be improved by ICI combination immunotherapy. A potential combination identified was nivolumab‐ipilimumab‐sargramostim. Most ICI combinations, however, produced a higher rate of adverse events compared with ICI monotherapy.